(untitled) (Journal of the Sylhet Agricultural University, 2026)
Over the last few decades, river ecosystems have been increasingly degraded by natural and human-induced pressures, leading to serious consequences for fish biodiversity and fishers’ livelihoods. The Kalni River ecosystem has been severely affected by climate-related factors such as rainfall variability, temperature fluctuations, and flash floods, as well as anthropogenic activities including overfishing, destructive fishing gear, and water pollution. A six-month field survey (December 2023–May 2024) involving 100 randomly selected fishers was conducted using structured questionnaires and interviews. The results showed that 82% of fishers experienced livelihood losses due to declining fish diversity, with 65% reporting severe impacts. Daily fish catch declined across seasons, with most fishers catching only 1.0–2.0 kg during pre-monsoon, 3.0–4.0 kg in monsoon, and 2.0–3.0 kg in post-monsoon periods. Reduced income limited households’ ability to support education; although primary school enrollment remained high (60% girls), dropout rates increased at higher levels due to financial constraints. Housing conditions improved for 47% of respondents, while 43% reported no change and 10% experienced deterioration. Sanitation facilities remained unchanged for 43% of fishers, improved for 36%, and declined for 10%. Health services deteriorated for 51% of households, and declining income forced 82% of fishers to depend on loans, compared to only 24% two decades ago. Overall, the decline in fish biodiversity has severely undermined the socioeconomic conditions and livelihood security of the Kalni River fishing community. J. Sylhet Agril. Univ. 12(2): 143-157, 2025